The Effect of Teacher Competence and Discipline on Students' Academic Achievement in Aqidah Akhlak at MI GUPPI 1 Sukapura - Ismi Maria Ulfa; Ihsan Mustofa; Jaenullah Jaenullah (CV. Bimbingan Belajar Assyfa, 2025)
This study aims to determine the influence of teacher competence and teacher discipline on students' learning achievement in Aqidah Akhlak at MI GUPPI 1 Sukapura, Sragi District, South Lampung Regency. The background of this research is based on the importance of the teacher's role in the learning process, particularly teacher competence and discipline, which can influence students' learning success. This is a quantitative study with a population of all students at MI GUPPI 1 Sukapura. The sampling technique used proportional random sampling with the Slovin formula, yielding 60 respondents from a total population of 71 students. Data collection methods included questionnaires and documentation. Data analysis employed multiple linear regression using SPSS. The results indicate that teacher competence, together with teacher discipline, significantly influences students' Aqidah Akhlak learning achievement. Hypothesis testing revealed a significance value for the simultaneous influence of teacher competence and discipline on student achievement with Fcount (28.831) > Ftable (4.46). The coefficient of determination (R²) of 0.892 indicates that 89.2% of the variation in student learning achievement can be explained by teacher competence and discipline, while 10.8% is explained by other factors. This research confirms that enhancing teacher competence and discipline is a key factor in improving student learning achievement in Aqidah Akhlak.